2018
DOI: 10.1038/s41598-018-22509-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity reduction in silicon fishbone nanowires

Abstract: Semiconductor nanowires are potential building blocks for future thermoelectrics because of their low thermal conductivity. Recent theoretical works suggest that thermal conductivity of nanowires can be further reduced by additional constrictions, pillars or wings. Here, we experimentally study heat conduction in silicon nanowires with periodic wings, called fishbone nanowires. We find that like in pristine nanowires, the nanowire cross-section controls thermal conductivity of fishbone nanowires. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 44 publications
3
50
0
Order By: Relevance
“…It means that κ = aN /(b + µN ), with a and b parameters independent of N and µ and depending on the other properties of the system, as discussed below. We underline that this behavior is in good qualitative agreement with most of experimental results concerning the size-dependent behavior of the thermal conductivity in nanosystems [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. It is also important to stress that, as anticipated, the conductivity is independent of the parameter α, proving that any particular choice of stochastic calculus is irrelevant to the physics of the system.…”
Section: Heat Conduction In the Mass-spring Chainsupporting
confidence: 85%
“…It means that κ = aN /(b + µN ), with a and b parameters independent of N and µ and depending on the other properties of the system, as discussed below. We underline that this behavior is in good qualitative agreement with most of experimental results concerning the size-dependent behavior of the thermal conductivity in nanosystems [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. It is also important to stress that, as anticipated, the conductivity is independent of the parameter α, proving that any particular choice of stochastic calculus is irrelevant to the physics of the system.…”
Section: Heat Conduction In the Mass-spring Chainsupporting
confidence: 85%
“…For instance, at room temperatures, the thermal conductivity of modulated nanowires was reduced from κ∼45 to κ∼28 W m −1 K −1 upon reducing the neck size from 122 to 45 nm. It was also observed that by increasing the difference between the smaller and larger cross-sectional dimension, a small reduction in thermal conductivities was obtained which was not predicted by phonon transport simulations [101]. At very small length scales, molecular dynamics simulations have suggested that by engineering modulations in nanowires of diameter d∼5 nm, strong reduction in thermal conductivity can be obtained due to the changes in the phonon dispersion relations caused by acoustic softening [103], which reduces the phonon velocities in nanostructures.…”
Section: Surface Modulated Nanowiresmentioning
confidence: 95%
“…In such step modulated nanowires, recent experimental measurements found that thermal conductivity is strongly determined by the size of the smaller nanowire section (i.e. neck) ( figure 7(a)) [101]. For instance, at room temperatures, the thermal conductivity of modulated nanowires was reduced from κ∼45 to κ∼28 W m −1 K −1 upon reducing the neck size from 122 to 45 nm.…”
Section: Surface Modulated Nanowiresmentioning
confidence: 98%
“…Measurements are represented by discrete data points, and results obtained by simulations are plotted by solid lines with dots. Adapted with permission . Copyright 2018, Springer Nature; the notation used is applicable only to this figure.…”
Section: Thermal Transport In Nanostructured Membranesmentioning
confidence: 99%
“…Adapted with permission. [96] Copyright 2018, Springer Nature; the notation used is applicable only to this figure.…”
Section: Npm Versus Npcmentioning
confidence: 99%